2019
DOI: 10.1007/s00521-018-3957-4
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical models and migrating birds optimization for robotic U-shaped assembly line balancing problem

Abstract: Modern assembly line systems utilize robotics to replace human resources to achieve higher level of automation and flexibility. This work studies the task assignment and robot allocation in a robotic U-shaped assembly line. Two new mixed integer programming linear models are developed to minimize the cycle time when the number of workstations is fixed. Recently developed migrating birds optimization (MBO) algorithm is employed and improved to solve large-sized problems. Problemspecific improvements are also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 48 publications
0
8
0
3
Order By: Relevance
“…Flexibility (Avikal et al, 2013;S ahin and Kellegöz, 2017) and re-configurability (Wang et al, 2009;Li et al, 2019) should be considered when designing a manufacturing system which should have the capability of adapting dynamic changes of product varieties and production volumes in a cost effective manner (Kara et al, 2011). Adapting these issues in manual assembly, WWALs are frequently used in industrial practices (Al-Zuheri et al, 2012;Wang and Bennett, 2014;Durmusoglu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexibility (Avikal et al, 2013;S ahin and Kellegöz, 2017) and re-configurability (Wang et al, 2009;Li et al, 2019) should be considered when designing a manufacturing system which should have the capability of adapting dynamic changes of product varieties and production volumes in a cost effective manner (Kara et al, 2011). Adapting these issues in manual assembly, WWALs are frequently used in industrial practices (Al-Zuheri et al, 2012;Wang and Bennett, 2014;Durmusoglu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Baykaso glu and Dereli (2009) proposed a novel algorithm which integrates ranked positional weight heuristic, computer method for sequencing operations for assembly lines algorithm and ant colony optimization for solving UALBP to minimize the number of stations. Moreover, migrating birds optimization (Li et al, 2019) and grey wolf optimization (Zhang et al, 2019) are proposed for robotic UALBP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Faced with increased labor cost and concerns of efficiency, one of the trend that is being adopted in industries are the replacement of the human workers with robots. U-shaped assembly line with robots to complete all the tasks are referred to as robotic U-shaped assembly line (Li et al, 2019a). This type of line will help to reduced labor cost, higher accuracy and higher stability.…”
Section: Nomenclaturementioning
confidence: 99%
“…The experiments showed that the SAs are superior to other algorithms under the same problem assumptions. In addition to the study of one-sided straight assembly line, Li et al proposed a discrete cuckoo search algorithm [13] and a migrating birds optimization [14] to solve the two-sided and U-type RALB problems, respectively. Moreover, there are also some papers considering the reduction of energy consumption brought by robots in robotic assembly lines [15][16][17].…”
Section: Introductionmentioning
confidence: 99%